Água residuária de suinocultura e sistema plantio direto: Efeitos sobre atributos do solo, desenvolvimento e nutrição do milho. - Polido, Guilherme Pereira (2021)
Swine wastewater (ARS) is generated in large quantities on swine farms, and this residue has a high organic load that, if well managed, provides water and nutrients for crops and, by associating its use with conservationist forms of soil management, as the no-tillage system, can be a sustainable alternative for the recovery of degraded areas and maintenance of water and nutrients in the soil. In this sense, this work sought to highlight two premises: i) the establishment of a conservationist management system together with the increase of different depths of swine wastewater provide changes in the chemical and physical properties of the soil and; ii) the use of irrigation with ARS in conjunction with the no-tillage system provides an increase in the development and mineral nutrition of corn. In view of the proposed, the objective of this work was to evaluate the potential of the agricultural use of ARS in the irrigation of corn, cultivated in different irrigation depths and soil management systems, through the morphoagronomic parameters of corn, as well as on the attributes chemical and physical properties of the soil and on the foliar contents of macro and micronutrients in field work. The experiment consisted of two soil management systems, conventional tillage system (SPC) and no-tillage system (SPD), and five irrigation depths with ARS (50%, 75%, 100%, 125%, and 150% of the real evapotranspiration-ETc of the maize crop), with three replications and implanted in a 5x2 factorial scheme cultivated in strips. The present study, conducted in the experimental area of Ifes - Campus de Alegre, is part of a project started in 2017 where two cycles of corn cultivation have already been conducted. The data presented represent the results of the third cropping cycle in the same experimental area. During the maize development cycle, leaves were collected at the tacking stage to determine the leaf contents of N, P, K, Ca, Mg, Cu and Zn. The evaluation of the morphoagronomic parameters of corn was performed when the plants were at an appropriate stage for silage. At the end of the corn cycle, soil samples were collected in the 0-10, 10-20 and 20-40 cm layers for further chemical and physical analysis of the objects under study. In general, the ARS depths provided the highest significant means for the chemical attributes tested if observed under conventional soil management. Most chemical attributes showed some difference between the averages obtained in the comparison between SPC and SPD in the ARS slides tested. However, at 0 to 10 cm depth this did not occur for potassium, sodium, H+Al and TOC; at a depth of 10 to 20 cm there was no difference in the values of pH, Na, H+Al, Zn and TOC; and at a depth of 20 to 40 cm there was no difference for pH, Na, Al, H+Al, Cu, Fe and COT which were not influenced by any of the management systems adopted. In general, there was no difference between the averages obtained for the physical attributes analyzed in the comparison between the management systems and in the ARS blades applied at the different investigated depths. Soil management systems did not influence the foliar contents of the evaluated nutrients, with the exception of Ca, which showed the highest levels in all ARS depths in the SPC. Ear weight in green mass (PEMV) and plant dry mass (MSP) responded linearly to the increase in ARS blades, proving the positive effect of ARS in increasing the production of plant material for silage production, in addition to favoring the increase in AP, AIE, DC and MFP.